Building a sustainable risk culture using the six areas of discipline: Analysis from FCA - Endeley, E.L. (2016)
The financial services industry has constantly been under the spotlight over the last two decades as a result of mass financial losses, and a complete failure in managing operational risks. The extensive focus on operational risk has brought us towards the direction of the fairly new term ‘Risk Culture’, as it has been identified by researcher, scholars, consulting firms, regulatory bodies, etc., to be a key aspect of managing and preventing operational risk. This has resulted to ‘risk culture’ especially in financial institutions to be one of the most dominant topics in this modern age. Although influential practitioners such as the Institute of Risk Management (2012), McConnell (2008), etc., have developed theories and framework concerning risk culture, this paper aims to examine how we can maintain an effective and sustainable risk culture by using the system created by PWC (2014) that is set to influence organizational culture. The aim of this paper is to examine the extent to which this systematic framework can be applied in practice by conducting a qualitative content analysis using the Financial Conduct Authority Final Notices placed on financial institutions as evidence. The study will try to find if there is a correlation between the framework and evidence in real life, in order to evaluate the extent it can be used to create an effective and sustainable risk culture. The analysis does find evidence of correlation assuring its strength, however, there is still room for improvement to attain more accurate outcomes. A Possible suggestion recommended is to expand the dimensions in relation to people risk.